A New [2+2+1] Heterocyclization for the Synthesis of 2,3,5-Trisubstituted Thiophenes under Microwave Irradiation - Xu, Hai-Wei; Ma, Guan-Hua; Jiang, Bo; Tu, Shu-Jiang (Synthesis, 2013)
A new three-component strategy for the efficient synthesis of 2,3,5-trisubstituted thiophene derivatives through a [2+2+1] heterocyclization between 3-(2-aryl-2-oxoethylidene)-2-oxindoles and α-thiocyanato ketones under microwave irradiation is described. The bond-forming efficiency, accessibility, and generality of this synthesis make it highly valuable to assemble thiophene scaffolds.
Keywords: heterocyclization; substituted thiophene; three-component reactions; α-thiocyanato ketone; 3-(2-aryl-2-oxoethylidene)-2-oxindole